(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The subject matter in this article is the principle of “full harmonization” in European contract law. The main idea in studying this issue, is to analyze the advantages and disadvantages of the implementation of the principle of “full harmonization” in this area, versus the principle of “minimum harmonization,” and, to bring them into the line with the benefits in the functioning of common European market, the degree of efficiency in the protection of contracting parties, the scope of market competitiveness on goods and services, and the impact on the volume and dynamics of cross-border transactions.